(untitled) (Research, Society and Development, 2023)
Currently, there has been a significant increase in diagnoses of mental disorders, which have a great impact in terms of morbidity, impairments in functionality and a decrease in the quality of life of their patients, since approximately 90% of mental health problems present manifestations of depression, anxiety, insomnia, fatigue, irritability, memory and concentration dysfunction. The objective of this study was to analyze the difficulties experienced by patients during the treatment of mental disorders and the importance of pharmaceutical assistance for good adherence to their pharmacological treatment. An integrative literature review was carried out on problems during treatment with psychotropic drugs and the importance of pharmacotherapeutic guidance for good adherence to treatment. The analysis and interpretation of the results obtained was carried out through interpretation and inference and consisted of presenting the selected studies and explaining the categories defined for analysis. 42 articles were identified in the search on electronic platforms. Six were excluded due to publication date, 4 due to language other than Portuguese and English and 5 due to incomplete or duplicate text that did not address the topic, resulting in 27 articles for abstract evaluation. At this stage, 7 articles that did not address the research question were excluded, 20 studies for reading the full text selected and included in this review. The study concluded the importance of the work of the pharmacist in pharmacotherapeutic orientation in mental health.